2021
DOI: 10.1002/pol.20210524
|View full text |Cite
|
Sign up to set email alerts
|

Improving the efficiency and sustainability of catalysts for direct arylation polymerization (DArP)

Abstract: In the past decade, direct arylation polymerization (DArP) has rapidly developed as a sustainable synthetic protocol for cost-effective, atom-economical preparation of conjugated polymers. By circumventing monomer functionalization with toxic transmetallating reagents such as organostannane and organoboron required for Stille-Migita and Suzuki-Miyaura polymerization methods, DArP proceeds through a metal-catalyzed C H activation pathway for the preparation of highperformance conjugated polymer materials. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 232 publications
0
24
0
Order By: Relevance
“…91,92 Choices of ligands, catalytic systems, additives, and solvents are shown to help minimize the defects. 93,94…”
Section: Polymerization Methodsmentioning
confidence: 99%
“…91,92 Choices of ligands, catalytic systems, additives, and solvents are shown to help minimize the defects. 93,94…”
Section: Polymerization Methodsmentioning
confidence: 99%
“…23−26 Moreover, the recyclability of SiliaCat DPP-Pd has previously been showcased in various small-molecule Stille and Suzuki coupling reactions and further extended to large-scale synthesis in commercial flow reactors. 25−27 Although Leclerc et al have previously demonstrated the high reactivity of this heterogeneous catalyst in DArP using Ozawa-derived conditions (i.e., in nonpolar solvents), 8,18 our preliminary efforts revealed that the recovered SiliaCat DPP-Pd was not reusable after the initial polymerization under similar conditions (see SI for details). This may be attributed to the longer reaction time usually required for these polymerizations (24 h or more) compared to those for small-molecule cross-coupling reactions (∌30 min), 25,26 which likely results in significant leaching of Pd from the solid support suppressing the catalytic activity of the recovered Pd species.…”
mentioning
confidence: 85%
“…Specifically, the generation of stoichiometric, highly toxic organotin byproducts and a multistep preparation of unstable stannylated monomers makes Stille impractical for the large-scale synthesis of CPs. 8 In recent years, direct arylation polymerization (DArP) has emerged as a facile synthetic tool for the preparation of highquality CPs through an atom-economical C−H activation pathway, alleviating the need for hazardous, pyrophoric reagents, and reducing toxic waste production (Scheme 1a). 8−10 Recent advances in replacing traditional, hazardous solvents with biorenewable green alternatives such as cyclopentyl methyl ether (CPME) and p-cymene have further enhanced the sustainability of DArP protocols.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A wealth of information on DArP can be found in the numerous review articles previously published. − Topical review articles are also available, addressing topics such as defects in DArP-produced polymers , and improving DArP’s sustainability. − To ameliorate the existing literature, this perspective article presents a strategy in developing new methodologies for conjugated polymer synthesis. DArP is focused on as a useful example, with guidance on how to adapt existing small molecule methodologies to develop novel polymerizations.…”
Section: Introductionmentioning
confidence: 99%